THE MULTILATERAL COLLECTIVE GUARANTEES IN MODERN WORLD ORDER: INTERNATIONAL EXPERIENCE AND UKRAINIAN CONTEXT - Krysenko, O. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
Political and legal history as well as geopolitical phenomenology of such thing as multilateral collective guarantees are studied. The contradictory nature of their political declarations and the impact of their existence on the reproduction of the rules of domination in world politics as well as on the maintenance of world order is analyzed. The existing state of multilateral security guarantees for Ukraine on the basis of the Budapest Memorandum after the annexation of Crimea and the occupation of Donbass territories is examined. The ways to reduce the negative effects of quasi-juridical status of the Budapest Memorandum for Ukraine is outlined.